Examining the Role of Attribution and Intercultural Competence in Intercultural Service Encounters - Tam, J.L.; Sharma, Piyush; Kim, N. (Emerald Group Publishing, 2014)
Purpose – This study aims to develop a model based on attribution theory and intercultural literature to explain the underlying customer satisfaction process in intercultural service encounters. Design/methodology/approach – In-depth interviews were used to develop an understanding of customer experience and evaluations in intercultural service encounters. A quasi-experiment with 236 customers was used to empirically examine the relationships between perceived culture distance, cultural attribution, intercultural competence and customer satisfaction. Findings – Perceived culture distance is positively related to customer satisfaction, with cultural attribution mediating the relationship between perceived cultural distance and customer satisfaction, and partially mediating the moderating effect of intercultural competence on the relationship between perceived culture distance and customer satisfaction.Research limitations/implications – This study focuses on cultural attribution in intercultural service encounters. It is acknowledged that there are other attribution dimensions such as stability and controllability which may interact with perceived culture distance and influence subsequent customer satisfaction evaluation. Future research should consider these various dimensions and examine their mediating role in customer satisfaction. Practical implications – It is recommended that service firms educate their customers of diverse cultures about local norms and practices, and proactively manage their expectations throughout the service experience. Originality/value – Despite the growing importance of intercultural service encounters, the findings of the relationship between perceived cultural distance and customer satisfaction are mixed. This study contributes to the literature by advancing our theoretical knowledge and empirical evidence of the role of cultural attribution and intercultural competence in intercultural service encounters.